Peranan Kebebasan Akademik dalam Penyelamatan Sumber Daya Alam dan Antropologi Budaya - Basuki Wasis; Herlambang Perdana Wiratraman; Roedy Haryo Widjono (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2021)
Saving natural resources, protecting the environment and preserving local culture is a tough job given the complexity of the problem. The way to uncover problems and environmental crimes and destroyers of natural resources is by "Scientific Evidence" or "Scientific Approach". The role of academic freedom and civil liberties is very much needed in environmental protection, natural resource management and preservation of local culture. Academic freedom must always hold on scientific evidence and the basic principles of academic freedom. Surabaya's five basic principles of academic freedom can be used to develop the Tri Dharma of Higher Education. Civil liberties can hold on to state regulations and local customs or culture. Experts (academics) and local environmental and cultural activists must be protected from acts of legal terror or the Strategy of Law Swiet Again Public Partipation (SLAPP)". Academic freedom and civil liberties must be maintained and developed for sustainable development, natural resource management, environmental protection and preservation of local culture. The Bedouin, Dayak, Balinese, Javanese, Minang, Acehnese, Sundanese, Batak, Bugis, Papuan and other cultures in protecting the environment and local culture should be an example or model. In practice the tribe can maintain local culture because it maintains a space for civil liberties called "deliberation and consensus" and maintains communication between groups or tribes with the principle of "Unity in Diversity" for the creation of "A Fairness or Social Justice".